Phenytoin Inhibits the Persistent Sodium Current in Neocortical Neurons by Modifying Its Inactivation Properties - Colombo, Elisa (Public Library of Science, 2013)
The persistent Na(+) current (I(NaP)) is important for neuronal functions and can play a role in several pathologies, although it is small compared to the transient Na(+) current (I(NaT)). Notably, I(NaP) is not a real persistent current because it undergoes inactivation with kinetics in the order of tens of seconds, but this property has often been overlooked. Na(+) channel blockers, drugs used for treating epilepsy and other diseases, can inhibit I(NaP), but the mechanism of this action and the conditions in which I(NaP) can be actually inhibited have not been completely clarified yet. We evaluated the action of phenytoin (PHT), a prototype anti-epileptic Na(+) channel blocker, on I(NaP) inactivation in pyramidal neurons of rat sensorimotor cortical slices at different concentrations, from 5 to 100 µM. PHT did not modify I(NaP) evoked with depolarizing voltage ramps of 50 or 100 mVs(−1), but decreased I(NaP) evoked by slower voltage ramps (10 mVs(−1)). However, at all of the tested concentrations, PHT decreased I(NaP) evoked by faster ramps when they were preceded by inactivating pre-pulses. Moreover, PHT shifted towards negative potentials the voltage-dependence of I(NaP) inactivation and accelerated its kinetics of development also at depolarized potentials (+40 mV), not consistently with a simple inactivated state stabilizer. Therefore, our study shows a prominent PHT effect on I(NaP) inactivation rather than an open channel block, which is instead often implied. I(NaP) is inhibited by PHT only in conditions that induce major I(NaP) inactivation. These results highlight the importance of I(NaP) inactivation not only for physiological functions but also as drug target, which could be shared by other therapeutic drugs. Through this action PHT can reduce I(NaP)-induced long-lasting pathological depolarisations and intracellular sodium overload, whereas shorter I(NaP) actions should not be modified. These properties set the conditions of efficacy and the limits of PHT as I(NaP) inhibitor.